ISLAM, BUDAYA KORUPSI DAN GOOD GOVERNANCE - Fawaid, Ahmad (KARSA Journal of Social and Islamic Culture, 2012)
Abstract The phenomenon and corruption action still becomes a fact that cannot be finished. One of causes is mentality of the world. It makes the cause why corruption becomes a massive culture. Beside restraining orientation of the world, good governance must become the priority. The result is that corruption does not become the culture anymore, and slowly but sure, it can be eliminated, or at least it can decrease. Kata-kata kunci korupsi, budaya korupsi, indeks persepsi korupsi, good governance